Designing factors to improve verbal ability among children with autism in Subang Jaya, Malaysia - Hosseinioun, Asiehsadat; Mohd Dolah, Shahrizal (Science Research Society (SRS), 2022)
This study analyzed the knowledge and implementation of a suitable approach for children with autism to improve their language delay and speech problem, which is related to communication and behavior patterns. It aimed to improve kids with autism who has speech difficulty by proposing the idea of a new device to increase their communication, social skills, and behavior pattern. Thus, it identified a current method to practice speaking with kids to improve the ability to talk, and besides that, to increase the patterns of behavior. Based on the theory of mind which shows how a mind can control a specific subject and part a conceptual framework had been suggested. The research used observation, and survey methods to evaluate the findings. The result is the impaired a kid with mild autism’s ability to communicate and social skills. Thus, it shows the advantage of talking to others and increases the ability to communicate by user experience.